Relationship Between Anosmia, Interleukin-6, and Disease Course of SARS COVID-19 Infection - Georgiev, Konstantin; Pacholova, Yana; Mileva, Sevda; Georgieva Yordanova, Mariana; Shopov, Nikola (ENT Updates, 2022)
Background: Olfactory dysfunction became increasingly popular as an early symptom of COVID-19 infection, associated with a positive outcome and milder course of the disease. Initial studies suggest that interleukin-6 directly damages the olfactory bulb, thus playing an important role in the mechanism of anosmia. Higher plasma levels of interleukin-6, on the other hand, are related to the severe course of the disease after COVID-19 infection. Methods: The present study explores the predictive power and the relationship between anosmia and plasma levels of interleukin-6 in 122 patients who were hospitalized with COVID-19 in the period March to November 2021 in the Hospital Base for Active Treatment of Military Medical Academy, Varna, Bulgaria. Results: The positive correlation between plasma levels of interleukin-6 and disease severity was confirmed. Also, we observed a significant decrease in interleukin- 6 plasma levels during the course of the disease in patients with a favorable outcome. There was no statistically significant difference between plasma levels of interleukin-6 in recovered patients with and without anosmia. We also reported a high percentage of hospitalized and deceased patients with anosmia. Conclusions: In patients with moderate-to-severe SARS CoV-2 infection, anosmia has not been proven to be a prognostic sign for a positive outcome of the disease. However, our data show that plasma levels of interleukin-6 have good predictive power for the course and outcome of the infection. We found a positive correlation between interleukin-6 and the severity of the disease. Favorable outcome was most often preceded by a rapid drop in interleukin-6 levels.